PENGGUNAAN MEDIA PEMBELAJARAN APEL UNTUK MENGOPTIMALKAN KEMAMPUAN NUMBER SENSE SISWA DENGAN DOWN SYNDROME PADA MATERI BILANGAN ASLI - Tri Sulastri Gustiani, - (2022)
This research was conducted based on mathematics for all and the low number sense ability of students, especially students with disabilities. Number sense ability is the ability to understand numbers using intuition, starting from assessing the value of numbers, making estimates, doing mental computations, and assessing the fairness of the results. No research has been found that describes the number sense ability of students with down syndrome. The purpose of this study was to obtain information and a description of the number sense ability of students with down syndrome on natural numbers, the factors that influence it, and the effectiveness of using APEL learning media to optimize the number sense abilities of students with down syndrome on natural numbers. This research uses qualitative approach with a case study method conducted in one of the BC Category Special Schools at West Bandung Regency. Because the number sense ability is different for each individual, there is no influence from chronological age or grade level. The selection of participants was based on the results of a preliminary study related to mental ability and stability, as well as the parent's willingness. Data were collected through document study techniques, interviews, observations, and tests in the form of achievement tests before and after using the APEL learning media consisting of oral and written tests. The results showed that: a) students with the highest down syndrome had the number sense ability at level 2, with influencing factors including the limitations of students with down syndrome, learning motivation of students with down syndrome, support for studying at home by parents, students mood, learning strategies, and unpredictable conditions in the field; and b) APEL learning media is effective for optimizing the number sense ability of students with down syndrome in terms of increasing the achievement of number sense abilities of students with down syndrome during the learning process, activities, and relatively positive responses of students with down syndrome during learning, supported by the optimal number sense abilities achievement of students with down syndrome after using APEL learning media.